A Case of Non-Small Cell Lung Cancer with Mutually Exclusive EGFR and KRAS Mutations - Abhimanyu Tushir; Israh Akhtar; Anjali Seth (Current Issues in Molecular Biology)
Historically, EGFR and KRAS mutations were believed to be mutually exclusive. However, over the past few years, there have been emerging case reports showing the co-existence of both mutations in a single case. The majority of these co-occurring alterations were detected in samples collected from patients with resistance to tyrosine kinase inhibitor (TKI) treatment, indicating a potential functional role in driving resistance to therapy. These co-occurring tumor genomic alterations are not necessarily mutually exclusive, and evidence suggests that multiple clonal and sub-clonal cancer cell populations can co-exist and contribute to EGFR TKI resistance. We have reported such a case of concomitant EGFR and KRAS mutation in a 64-year-old female. This case highlights the importance of continuous molecular testing in managing NSCLC, especially in cases with rare mutation profiles. The emergence of new mutations during treatment can significantly impact the course of therapy and patient outcomes. In this case, the detection of both EGFR and KRAS mutations guided the selection of an appropriate targeted therapeutic strategy, including the use of Amivantamab.